Invasion of Nostocales (cyanobacteria) to Subtropical and Temperate Freshwater Lakes – Physiological, Regional, and Global Driving Forces - Sukenik, Assaf; Hadas, Ora; Kaplan, Aaron; Quesada, Antonio (Frontiers in Microbiology, 2012)
Similarly to the increased number of studies on invasive plants and animals in terrestrial and aquatic ecosystems, many reports were recently published on the invasion of Nostocales (cyanobacteria) to freshwater environments worldwide. Invasion and proliferation of Nostocales in new habitats have the potential to significantly alter the structure of native community and to modify ecosystem functioning. But most importantly, they influence the water quality due to a variety of toxic compounds that some species produce. Therefore a special attention was given to the invasion and persistence of toxic cyanobacteria in many aquatic ecosystems. Here we summarize the currently published records on the invasion of two Nostocales genera, Cylindrospermopsis and Aphanizomenon, to lakes and water reservoirs in subtropical and temperate zones. These invading species possess traits thought to be common to many invasive organisms: high growth rate, high resource utilization efficiency and overall superior competitive abilities over native species when local conditions vary. Assuming that dispersion routes of cyanobacteria have not been changed much in recent decades, their recent establishment and proliferation in new habitats indicate changes in the environment under which they can exploit their physiological advantage over the native phytoplankton population. In many cases global warming was identified as the major driving force for the invasion of Nostocales. Due to this uncontrollable trend, invasive Nostocales species are expected to maintain their presence in new habitats and further expand to new environments. In other cases regional changes in nutrient loads and in biotic conditions were attributed to the invasion events